Parental bond and aggressiveness in high school students - Asencios Julca, Miriam Esther (2019)
This study intends to analyze parental bond and aggressiveness in adolescents attending the first year of high school in a public educational institution located in San Juan de Lurigancho District, and the relationship between those variables. The sample consisted of 100 adolescents (12-13 years old). The instruments applied were the Behaviourally Anchored Rating Scales- BARS (Conger 1989), The Buss and Perry Aggression Questionnaire (modified by Matalinares, Yariñango, Uceda, Fernández, Huari, Campos, and Villavicencio, 2012), and a sociodemographic datasheet. The results show the lack of statistically significant relationship between the variables. The sample also shows a high rate of physical aggressiveness. Indeed, after the sample analysis, it was concluded that the influence of the adolescent’s social environment might explain the existence of such aggressive behavior.